2015
DOI: 10.1093/ejo/cjv015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the probiotic bacteriumLactobacillus reuterion white spot lesion development in orthodontic patients

Abstract: Daily intake of probiotic lozenges did not seem to affect the development of WSL during orthodontic treatment with fixed appliances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 27 publications
2
56
0
1
Order By: Relevance
“…Gizani et al [30] assessed the development of white spot lesions (WSL) on photographs [34], following the administration of lozenges containing Lactobacillus reuteri for a mean period of 17 months. The other three studies investigated gingival inflammation for a maximum period of 1 month, using gingivitis [33,35] or bleeding [36] indices.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Gizani et al [30] assessed the development of white spot lesions (WSL) on photographs [34], following the administration of lozenges containing Lactobacillus reuteri for a mean period of 17 months. The other three studies investigated gingival inflammation for a maximum period of 1 month, using gingivitis [33,35] or bleeding [36] indices.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Of the five included studies, three of them 22-24 reported significant differences between the treatment and the control groups; another declared significant decreases in the final counts of microorganisms compared to the start of treatment. 25 Only one study 26 reported no differences of any kind. (Table 2) The probiotic strains used in the selected articles were reported in four of the five studies.…”
Section: Resultsmentioning
confidence: 99%
“…The only study in which no decrease in Streptococcus mutans was reported was in the one published by Gizani et al 26 which had important methodological differences with respect to the studies previously published in the area. The probiotic concentration used (10 8 bacteria per strain used daily) is well below the recommended concentration used to evaluate its effect on the oral cavity.…”
Section: 41mentioning
confidence: 97%
“…It has been proved in clinical studies that toothpastes containing triclosan and zinc citrate reduce dental plaque [69]. In probiotics-related studies on orthodontics, a reduction in the amount of Streptococcus has been reported; however, no positive effect on white spot lesions has been observed [72,73].…”
Section: Chemical Methodsmentioning
confidence: 99%